Universal health coverage and COVID-19: recent developments and implications - Rabia Hussain; Sara Arif (Taylor & Francis Group, 2021)
Universal health coverage (UHC) is meant to access the key health services including disease prevention, treatment, rehabilitation, and health promotion. UHC varies according to demographics, epidemiology, and technology-based trends, as well as according to people's expectations. Globally, the transition towards UHC has been associated with the intent of improving accessibility and affordability of healthcare. The COVID-19 pandemic has disrupted the health systems of even the most developed economies of the world in an unprecedented manner. The situation is also very challenging for the countries with the existing health inequities as well as the countries with the developing healthcare systems. This has amplified the need to accelerate efforts to build strong and resilient health systems to achieve progress towards UHC. This commentary discusses a global overview of UHC in the wake of COVID19. It also highlights the initiatives taken by Pakistan to promote the goals of UHC.